(3cJGH aj GdWHs ((3eOjfI JhfS s)
(3ChdgG (B:s
(3UaI eYLhf GdfSHd ef GdcHO hGdeYOI hgh YOje GdefaYI UaI JQjGb jPjH GdMUGI hjfaY ef hLY GdcHO hGdUMGd s
(3BNQgG (B:s
(3cGf jYed GdbUjQ edc GdQhe CNdGWg SfHd gfOi hOGQUjfi hRfLHjd hbQfad hadad Je hced HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3hGdcJGH YHGQI Yf edJbW ef fSNI bOjeI ef ahGFO eLehYI ef cJH cHGQ GdCWHGA hGdCOhjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs